Multi-Valent Group 14 Chalcogenide Architectures from Ionic Liquids: 0D-[Cs@SnII4(GeIV4Se10)4]7− and 2D-[SnII(GeIV4Se10)]2− - Santner, Silke; Wolff, Alexander; Ruck, Michael; Dehnen, Stefanie (Chemistry - A European Journal, 2018)
In order to explore if and how salts comprising polycations and salts comprising polyanions might interact, the [AlBr4]− salt of the [Pt@Bi10]4+ cluster cation was added to the reaction mixture for the synthesis of the supersphere cluster anion [Ge24Sn36Se132]24− from Cs4[Ge4Se10]⋅H2O and SnCl4⋅5 H2O under ionothermal conditions at 120 °C. Indeed, the reaction yields two new compounds, depending on the cation of the used ionic liquid. Apparently, the polycation is not retained under the given conditions, but it acts as a reductant affording SnII. In a (C4C1C1im)+-based ionic liquid mixture, a unique supertetrahedral anion is obtained that embeds a Cs+ cation, 0D-[Cs@SnII 4(GeIV 4Se10)4]7−, while (C4C1im)+ cations stabilize an unprecedented ternary layered anion, 2D-[SnII(GeIV 4Se10)]2−. Test reactions with common sources of SnII did not afford the new compounds, indicating the necessity of an in situ reduction, for which the polycation seems appropriate.
CRIS-Team Scopus Importer:2022-04-14
Keywords: chalcogenides; ionic liquids; polyanions; polycations; supertetrahedral clusters